Understanding the Impact of Artificial Intelligence (AI) on Traditional Businesses in Indonesia - Khan, Muhammad Asif (The Indonesian Institute of Science and Technology Research, 2024)
The integration of artificial intelligence (AI) in Indonesia's business landscape has ushered in significant changes, presenting challenges and opportunities for traditional businesses across various sectors. Understanding the implications of AI is crucial for navigating these changes effectively. This study aims to investigate the transformative impact of AI on traditional Indonesian businesses, specifically analyzing the opportunities and challenges associated with AI adoption and its implications for business strategies and operations. Utilizing a qualitative method, this study examines the influence of AI technologies on traditional Indonesian businesses. The study compiles data from academic literature, industry reports, and real-world case studies to analyze the intricate dynamics between AI technologies and human behavior. The findings reveal that AI integration offers numerous opportunities for traditional businesses in Indonesia, such as enhanced operational efficiency, improved customer experience, and innovation potential. However, significant challenges, including high implementation costs, data privacy concerns, and the lack of skilled AI talent, hinder widespread adoption. Despite these challenges, businesses that successfully navigate them can gain a competitive advantage in the digital age. This study contributes to the existing literature by providing fresh insights into the transformative impact of AI on traditional Indonesian businesses. It synthesizes recent research findings and case studies, offering valuable guidance for businesses aiming to leverage AI for strategic advantage.